Strengthening the Role of Widyaiswara in Improving the Quality of Human Resources Towards the Smart ASN 4.0 Concept - Said Pariq (Jurnal Prajaiswara, 2021)
Widyaiswara occupied an important role in forming quality ASN including in realizing the Smart ASN 4.0 concept. Smart ASN who have the ability to master technology will push the Indonesian government system into a bureaucracy that is in line with the spirit of the industrial revolution 4.0. All types of public services can be implemented on a digital basis and integrated in such a way that public services become more optimal. Widyaiswara as one of the elements in the development of electronic-based civil servant competencies is required to have the ability to prepare needs at every stage of the training process. The training stage is the implementation of training and education and training evaluation and development. Digital competence is needed by widyaiswara to compile materials that will be used in e-learning at that stage. The role of widyaiswara must exist starting from planning, content creation and evaluation to ensure learning objectives are achieved.